Wastewater Treatment Plant Design for Batik Wastewater with Off-Site System Method in Ulu Gedong Sub-District, Jambi City - Solikhati Indah Purwaningrum; Huwan Syarifuddin; Addion Nizori; Yudha Gusti Wibowo (Universitas Diponegoro, 2023)
Batik is a cultural heritage of Indonesia in the form of textile crafts. The batik industry uses a lot of dyes that cause environmental pollution. The study results showed that Artisanal Small Scale Industry batik has yet to perform batik wastewater management to a technical standard. Design planning for batik wastewater management considers the conditions of wastewater discharge, dyes, characteristics of wastewater, the location to be served, and the location of Waste Water Treatment Plant. The design of the batik Waste Water Treatment Plant building is an equalization unit with dimensions of 4.6 m long, 2.3 m wide, and 4 m high, an anaerobic unit with dimensions of 10.5 m long, 4 m wide and 3.5 m high, a filtration unit with a diameter of 8 inches, 40 inches tall, control tub with dimensions of length 8 m, width 4 m, and height 3.5 m, and sludge drying bed with dimensions of length 15 m, width 15 m and height 1 m. The processing unit obtained water pollutant concentrations in the processed wastewater of 2.426 mg/L BOD, 0.543 mg/L of COD, and 0.0115 mg/L of TSS. This concentration shows that the WWTP design optimally reduce the pollutants in batik wastewater.